Prophylactic Role of Averrhoa carambola (Star Fruit) Extract against Chemically Induced Hepatocellular Carcinoma in Swiss Albino Mice - Ritu Singh; Jyoti Sharma; P. K. Goyal (Advances in Pharmacological Sciences)
Liver cancer remains one of the severe lethal malignancies worldwide and hepatocellular carcinoma (HCC) is the most common form. The current study was designed to evaluate the prophylactic role of the fruit of Averrhoa carambola (star fruit or Kamrak) on diethylnitrosamine- (DENA-) induced (15 mg/kg b.wt.; single i.p. injection) and CCl4-promoted (1.6 g/kg b.wt. in corn oil thrice a week for 24 weeks) liver cancer in Swiss albino mice. Administration of ACE was made orally at a dose of 25 mg/kg b.wt/day for 5 consecutive days and it was withdrawn 48 hrs before the first administration of DENA (preinitiational stage). CCl4 was given after 2 weeks of DENA administration. A cent percent tumor incidence was noted in carcinogen treated animals while ACE administration resulted in a considerable reduction in tumor incidence, tumor yield, and tumor burden. Further, ACE treatment brings out a significant reduction in lipid peroxidation (P<0.001) along with an elevation in the activities of enzymatic antioxidants (superoxide dismutase, P<0.001, and catalase, P<0.001), nonenzymatic antioxidant (reduced glutathione, P<0.001), and total proteins (P<0.001) when compared to the carcinogen treated control. These results demonstrate that ACE prevents the DENA/CCl4 induced adverse physical and biochemical alterations during hepatic carcinogenesis in mice. This study suggests the prophylactic role of Averrhoa carambola against hepatocellular carcinoma in mice; therefore, it could be employed for the further screening as a good chemopreventive natural supplement against cancer.